Temporal profiling of haptoglobin and cytokines in feedlot cattle with bovine respiratory disease - Chitko-McKown, Carol G.; Engle, Bailey N.; Bennett, Gary L.; Kuehn, Larry A.; DeDonder, Keith D.; Apley, Michael D.; Harhay, Gregory P.; Clawson, Michael L.; White, Brad J.; Larson, Robert L.; Capik, Sarah F.; Lubbers, Brian V. (Frontiers in Veterinary Science, 2026)
Inflammatory cytokines and haptoglobin (HPT) were measured from 28 head of cattle that presented with bovine respiratory disease after being purchased and shipped to a common feedlot and assigned to either control or metaphylaxis treatment groups. Blood samples were obtained on the day of purchase (D0) and again at the time of diagnosis (S0) and 5 days after treatment (S5). Plasma was harvested and stored at −80 °C until assayed for the cytokines IFN-γ, IL-1β, IL-6, TNF-α, and HPT. Our objectives in this study were to determine differences between baseline (D0), day of diagnosis (S0) and post-treatment (S5), as well as to identify correlations among cytokine and HPT concentrations over time and by treatment. Interferon-gamma and IL-1β concentrations did not differ between D0 and S0 or S5. Tumor necrosis factor-α concentrations differed between D0 and both S0 and S5; however, no differences were observed between S0 and S5. Interleukin-6 and HPT concentrations differed between D0 and S0, D0 and S5, and between S0 and S5. Neither control nor metaphylactic treatment significantly impacted cytokine or HPT concentrations, nor did the state of origin. The strongest significant correlations among cytokine-timepoint combinations were observed for IL-1β and TNF-α S0 (0.93), and S5 (0.91). Both IL-6 and HPT increased from baseline to the time of BRD diagnosis and treatment, and HPT exhibited the most rapid decline after treatment (S5), suggesting that it may be the most useful single measurement for indicating both sickness and resolution post-treatment.